Clinical perspectives on the management of common psychiatric disorders in India - Reddy, M. S.; Mohandas, E.; Vaishnav, Mrugesh; John, Philip; Kumar, Suresh; Garg, Uttam; Shah, Bharat; Das, Jayanta (International Journal of Advances in Medicine, 2022)
Psychiatric disorders are common health problems in patients of all age groups, under-diagnosis and under-treatment of these disorders can result in disability and serious complications. With an objective of creating a comprehensive evidence-based consensus on common mental health disorders and their management in the Indian setting, 10 expert groups meetings involving 98 psychiatrists across India were conducted in the month of May 2020. Clinical insights related to burden, signs and symptoms, diagnosis and management were summarized based on the discussions during these meetings. Experts agreed that depressive disorders and anxiety disorders represent two important psychiatric disorders in India. Selective serotonin reuptake inhibitors (SSRIs) are commonly used for the treatment of depression. Benzodiazepines are effective for the treatment of comorbid anxiety in patients with depression, but their long-term use causes adverse events such as dependence and withdrawal reaction. Obsessive compulsive disorder (OCD), bipolar disorder, substance use especially alcohol withdrawal syndrome, and sleep disorders are other common psychiatric disorders found among Indian patients. Lithium and valproate represent the commonly used and effective pharmacological treatments for bipolar disorder. SSRIs are preferred drugs in the treatment of OCD, whereas benzodiazepines such as chlordiazepoxide and diazepam represent important pharmacological treatment options for alcohol withdrawal. Early identification and timely and effective treatment of psychiatric disorders is important for prevention of complications. Treatment should be individualized based on efficacy, tolerability profile of the medicine, risk of drug interactions, and cost. This consensus may be useful to psychiatrists and general practitioners treating common psychiatric conditions in Indian patients.